2021
DOI: 10.6004/jnccn.2020.7659
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors Associated With Rapid Relapse in Triple-Negative Breast Cancer: A Multi-Institution Study

Abstract: Background: Triple-negative breast cancer (TNBC) accounts for disproportionately poor outcomes in breast cancer, driven by a subset of rapid-relapse TNBC (rrTNBC) with marked chemoresistance, rapid metastatic spread, and poor survival. Our objective was to evaluate clinicopathologic and sociodemographic features associated with rrTNBC. Methods: We included patients diagnosed with stage I–III TNBC in 1996 through 2012 who received chemotherapy at 1 of 10 academic cancer centers. rrTNBC was defined as a distant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…As the ESME cohort focuses on patients with metastatic breast cancer, information on localized stage is often lacking, such as initial staging, specific treatment received such as platinum and biology as well as socioeconomic data, which limits analysis of predictors from early relapse. However, these factors have already been widely demonstrated in two previous cohorts (29,30). Also, several data, especially pathological and biological, are not present in ESME.…”
Section: Discussionmentioning
confidence: 90%
“…As the ESME cohort focuses on patients with metastatic breast cancer, information on localized stage is often lacking, such as initial staging, specific treatment received such as platinum and biology as well as socioeconomic data, which limits analysis of predictors from early relapse. However, these factors have already been widely demonstrated in two previous cohorts (29,30). Also, several data, especially pathological and biological, are not present in ESME.…”
Section: Discussionmentioning
confidence: 90%
“…TNBC patients are less likely to be diagnosed in a screening mammography, leading to diagnosis being made at a more advance stage [ 11 , 14 ]. Moreover, In Latin America most cases are diagnosed in advanced stages due to the serious problem of limited access to breast cancer screenings in these countries [ 15 , 16 ] Asad et al found that the stage at diagnosis was the most significant factor for the rapid development of relapse of TNBC; with 55% of patients with stage III TNBC at diagnosis developing relapse, demonstrating a 15-fold higher probability of relapse compared to women with stage I [ 17 ]. The majority of our patients (78.1%) have a histologic grade III.…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic factor analysis by Daniel G. Stover et al. found that RR-TNBC patients were associated with Medicaid/indigent insurance, being single, of Black ethnicity, having a lower income, and a younger age at diagnosis ( 28 , 29 ). Due to a lack of data, we did not focus on the analysis of many sociodemographic factors.…”
Section: Discussionmentioning
confidence: 99%